Caracterizações física e mecânica de pavimentos permeáveis para drenagem urbana - Vaz, Diego Alexandre (2021)
The lack of planning in the urbanization process of cities can bring a role of problems such as soil sealing, leading to the reduction of the absorption surfaces, causing an increase in the flow of rainwater and the occurrence of flooding and flooding. As a result, on days of intense rain, traffic on the streets of many cities is reduced or impossible, buildings are damaged and the population can still suffer material and financial losses, and even become infected with diseases. Therefore, this work aimed to verify the feasibility of using pervious concrete pavements as an alternative for urban drainage. For the development of the research, pervious concrete specimens were produced, with a mix of 1:4, by mass, with different water/cement ratios (w/c) and granulometric compositions, which were evaluated for water absorption, index of voids, specific mass, compressive strength, tensile strength by diametrical compression and permeability and flux coefficient. The results obtained showed that, for the three granulometric compositions, gravel 0, gravel 1 and mixed gravel (B0, B1 and BM), the increase in the w/c ratio resulted in an increase in compressive and tensile strength, in a reduction in the void ratio, and consequently in a reduction in the permeability index and concrete flow. Regarding the influence of particle size compositions on the properties of concrete produced with the same w/c ratio, the results showed that gravel 0 provided a concrete with better surface finish, gravel 1 provided a more pervious concrete and mixed gravel provided a concrete with higher resistance values. Based on the results, it was concluded that pervious concrete presented itself as a sustainable alternative to traditional urban drainage, being able to be used in sidewalks and sidewalks, where there is no heavy traffic.